A two-phase linear programming approach for redundancy allocation problems - Hsieh, Y.-C. (Yugoslav Journal of Operations Research; Vol 12 No 2 (2002): Vol. 12 No. 2, 2016)
Provision of redundant components in parallel is an efficient way to increase the system reliability, however, the weight, volume and cost of the system will increase simultaneously. This paper proposes a new two-phase linear programming approach for solving the nonlinear redundancy allocation problems subject to multiple linear constraints. The first phase is used to approximately allocate the resource by using a general linear programming, while the second phase is used to re-allocate the slacks of resource by using a 0-1 integer linear programming. Numerical results demonstrate the effectiveness and efficiency of the proposed approach.